2014
DOI: 10.1039/c3an01561k
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC UHD Q-TOF MS/MS analysis of the impact of sulfur fumigation on the chemical profile of Codonopsis Radix (Dangshen)

Abstract: Over recent decades sulfur fumigation has been becoming abused in processing some freshly harvested Chinese medicinal herbs, although it is questioned whether sulfur fumigation can result in changes in efficacy and safety of the herbs. One of the herbs commonly processed by sulfur fumigation is Codonopsis Radix (Dangshen). A report showed that lobetyolin content in sulfur-fumigated Dangshen was lower than in air-dried Dangshen. Whereas there is no investigation designed to compare the chemical profiles of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 10 publications
(3 reference statements)
0
52
0
1
Order By: Relevance
“…Besides residual sulfur dioxide, understanding the chemical changes of the key active ingredients in the herbs induced by sulfur fumigation is also crucially important. Such chemical alteration of TCMs has been evidenced undoubtedly by increasing numbers of studies, involving sulfur-fumigated white peony roots [4][5][6], white ginseng [7], Angelicae dahuricae radix [8], Fritillariae thunbergii bulbus [9], Chrysanthemi flos [10,11] and Codonopsis radix [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides residual sulfur dioxide, understanding the chemical changes of the key active ingredients in the herbs induced by sulfur fumigation is also crucially important. Such chemical alteration of TCMs has been evidenced undoubtedly by increasing numbers of studies, involving sulfur-fumigated white peony roots [4][5][6], white ginseng [7], Angelicae dahuricae radix [8], Fritillariae thunbergii bulbus [9], Chrysanthemi flos [10,11] and Codonopsis radix [12].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] were distributed at the right of the plot, while the sun-dried samples (Nos. [11][12][13][14][15][16] were at the left of the plot ( Figure S1a). The results of partial least squares (PLS) displayed a similar plot.…”
Section: Introductionmentioning
confidence: 99%
“…One report showed that lobetyolin content in sulfur-fumigated Dangshen was lower than that in air-dried Dangshen (Li et al 2010a). In our previous research, significant chemical differences between the organic solvent extracts of sulfur-fumigated and air-dried Dangshen samples were observed (Ma et al 2014). Components of the volatile oil from Dangshen exhibit various bioactivities (Sun et al 2008, Li et al 2010b, Jiang 2001).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, some reports showed that sulfur fumigation might cause chemical transformation of original components in the herbs, and consequently affect the clinical efficacy and safety of the herbs (Li et al 2012, Cao et al 2014, Jiang et al 2013, Wang et al 2014. Dangshen, a well-known traditional Chinese medicinal herb with Qi (氣) and Yin (陰) tonifying properties (Ma et al 2014), is usually processed by sulfur fumigation after harvest. Recently, some studies have demonstrated that sulfur fumigation causes dramatic variations in the chemical profiles of Dangshen.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the reality might be different. Besides existing in unconjugated forms, sulfur dioxide could easily react with existing moisture to generate free sulfurous acid (Jiang, Huang, Zheng, & Chen, 2013); more importantly, involve in chemical transformation of many original bioactive components in herbs potentially by esterification and/or addition reactions Li et al, 2012;Ma et al, 2014). Given these facts, it could be inferred that variations in residual sulfur dioxide content during sulfur-fumigation should be more complicated than expected, and there may be some relationship with changes in the original components in the herb.…”
Section: Introductionmentioning
confidence: 99%